PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN POWERPOINT INTERAKTIF TERHADAP PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Novandi, Mas; Hartoyo, Agung; Suratman, Dede (Universitas Tanjungpura, 2026)
This study aimed to analyze the effect of the Discovery Learning model assisted by interactive PowerPoint media on elementary school students’ conceptual understanding and critical thinking skills. The research employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The sample consisted of 44 students divided into an experimental group and a control group. The research instrument was an essay test that had been validated and proven reliable. Data were analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results revealed a significant difference between the experimental and control groups in both conceptual understanding and critical thinking skills, with a significance value of < 0.05. The mean score of the experimental group was higher than that of the control group. These findings indicate that the implementation of Discovery Learning assisted by interactive PowerPoint media is effective in improving students’ conceptual understanding and critical thinking skills. This model can serve as an innovative instructional alternative to enhance learning quality in elementary education